1991
DOI: 10.1210/jcem-72-1-51
|View full text |Cite
|
Sign up to set email alerts
|

Dual Defects in Pulsatile Growth Hormone Secretion and Clearance Subserve the Hyposomatotropism of Obesity in Man*

Abstract: We have examined the mechanisms underlying reduced circulating GH concentrations in the obese human. Computer-assisted (deconvolution) analysis was used to determine endogenous GH secretory and clearance rates quantitatively from entire 24-h plasma GH concentration profiles. These analyses revealed that the half-life (t 1/2) of endogenous GH was significantly shorter in obese (11.7 +/- 1.6 min) than in normal weight subjects (15.5 +/- 0.81 min; P less than 0.01). The accelerated blood disposal rate of GH was n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
259
4
9

Year Published

1993
1993
2011
2011

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 469 publications
(279 citation statements)
references
References 50 publications
7
259
4
9
Order By: Relevance
“…32 In addition, in obese subjects an increased GH metabolic clearance rate has been described. 33 Although mechanisms have not been fully elucidated, there is evidence that elevated FFA levels and increased insulin levels may play a pivotal role in determining reduced GH levels in obesity. Therefore, it is realistic to speculate that similar mechanisms may play a role in obese PCOS women.…”
Section: Growth Hormone (Gh)-igfsmentioning
confidence: 99%
“…32 In addition, in obese subjects an increased GH metabolic clearance rate has been described. 33 Although mechanisms have not been fully elucidated, there is evidence that elevated FFA levels and increased insulin levels may play a pivotal role in determining reduced GH levels in obesity. Therefore, it is realistic to speculate that similar mechanisms may play a role in obese PCOS women.…”
Section: Growth Hormone (Gh)-igfsmentioning
confidence: 99%
“…[61][62][63] Measurements performed during sleep and over 24 h have shown that GH secretion in obese children is reduced not only under physiological conditions, but also following pharmacologic stimulation with insulin, clonidine, arginine, levodopa, glucagon, GH-releasing hormone, and opiate peptides, much like in children with GH deficiency. 64 Despite the reduction in circulating GH levels, obese children may have normal, increased or reduced, plasma IGF-I and GH-binding protein levels.…”
Section: Role Of Obesity and Leptin In Pubertal Growthmentioning
confidence: 99%
“…Diversos estudos já comprovaram que o aumento do IMC está relacionado a uma diminuição na meia-vida (46), na produção, na freqüên-cia e na amplitude (47) dos episódios secretórios do GH. De uma forma geral, a taxa de secreção e produção do GH diminui em 6% para cada unidade aumentada no IMC e é quase 4 vezes menor em pacientes obesos do que em controle normais (46). A diminuição na liberação do GH também já foi evidenciada em crianças (48) e adolescentes obesos (49) e correlaciona-se indireta-…”
Section: A Síndrome Metabólica E O Eixo Somatotróficounclassified